GPS signal derived precipitable water vapor and its applications in rainfall prediction - Manandhar, Shilpa (2019)
The atmospheric water vapor is generally expressed in terms of Precipitable water vapor (PWV). It is an important indicator of water vapor climatology and variability in the lower troposphere and related climate processes. Global Positioning System (GPS) satellite signals are used to derive PWV values with high spatio-temporal resolution which is available under all-weather conditions. The PWV values are derived using the delay information from GPS signals. The signal delays in the troposphere are divided into two categories; Zenith Hydrostatic Delay (ZHD) and Zenith Wet Delay (ZWD). The ZWD delay is caused by the water vapor of the atmosphere and PWV values are derived using these ZWD values.